Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/lubricants7030024
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Wavebands for Discriminating Oxidation Time of Engine Oil as Detected by FT-IR Spectroscopy

Abstract: Fourier Transform-Infrared (FT-IR) spectroscopy was used to analyze gasoline engine oil (SAE 5W20) samples that were exposed to seven different oxidation times (0 h, 24 h, 48 h, 72 h, 96 h, 120 h, and 144 h) to determine the best wavenumbers and wavenumber ranges for the discrimination of the oxidation times. The thermal oxidation process generated oil samples with varying total base number (TBN) levels. Each wavenumber (400–3900 cm−1) and wavenumber ranges identified from the literature and this study were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…By comparing the spectra of fresh engine oil and worn engine oil in the area of fingerprint FTIR spectra, several changes can be observed in the infrared bands. The bands with a peak at 1172 and 1156 cm −1 belong to the sulfonate detergent tension bands [38,39], and the bands with a peak at 970 cm −1 and 656 cm −1 belong to the ZDDP. RMSEC was 0.193 mg KOH.g −1 and RMSEP = 0.124 mg KOH.g −1 for ten external samples.…”
Section: Figure 3 Rmsecv Depending On the Number Of Principal Componentsmentioning
confidence: 99%
“…By comparing the spectra of fresh engine oil and worn engine oil in the area of fingerprint FTIR spectra, several changes can be observed in the infrared bands. The bands with a peak at 1172 and 1156 cm −1 belong to the sulfonate detergent tension bands [38,39], and the bands with a peak at 970 cm −1 and 656 cm −1 belong to the ZDDP. RMSEC was 0.193 mg KOH.g −1 and RMSEP = 0.124 mg KOH.g −1 for ten external samples.…”
Section: Figure 3 Rmsecv Depending On the Number Of Principal Componentsmentioning
confidence: 99%
“…The high content of oxidation products further contributes to an increase in the acidity of the oil leading to a corrosive effect and contributes to an increase in viscosity and carbon deposits. Anti-foaming additives are used to counter the effect of air in the oil, antioxidants are used to decrease the speed the oxidation [25,26].…”
Section: Airmentioning
confidence: 99%
“…A physical change that oxidation causes is that the viscosity of the oil rises depending on the amount of oxygen that is used up as a result of the process [7,8]. Based on the type of anti-wear components, sulfonate detergents, material antioxidants, carbonyl compounds, hydroxyl and so on, there is infrared radiation absorption at a characteristic wavelength in all of the covalent chemical bonds in organic molecules [9]. Maleville et al [8] showed how the process of oxidation is influenced by the aromatic and sulphur content as well as the composition of the oils because of the consumption of oxygen and thin film oxidation tests.…”
Section: Introductionmentioning
confidence: 99%
“…This includes determining of the scope of the oil tests using the FTIR method [13]. Literature survey shows that near wave numbers 860 cm −1 and 970 cm −1 is where absorption is the highest and this was related to the oxidation times and for each of these oxidation times, the absorbance rate was quite different from all of the other times [9]. The wavenumbers mentioned above are closer to the IR spectra and measurements of this can be easily taken with the UV spectroscopy method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation